Jobs in Springfield, Massachusetts: Understanding and remedying the causes of low resident employment rates - Yolanda K. Kodrzycki; Ana Patricia Mu\~noz; Lynn Browne; DeAnna Green; Marques Benton; Prabal Chakrabarti; Richard Walker; Bo Zhao (Federal Reserve Bank of Boston, 2010)
As part of the Federal Reserve Bank of Boston's commitment to supporting efforts to revitalize the economy of Springfield, Massachusetts, this paper explores the causes of and potential remedies for the city's low resident employment rates. When compared to the state as a whole and to other midsize New England cities, the share of employed city residents is low, particularly for residents of downtown Springfield and its nearby neighborhoods. By analyzing the availability of jobs across Springfield's various neighborhoods and in nearby towns and cities, this paper's goal is to learn why so few Springfield residents are employed, and thus to identify policy priorities to increase employment. This study finds that solving Springfield's low resident employment rates will require a combination of new job creation, improved informational and physical access to jobs, and strengthening the citizenry's job skills.
Keywords: J21; R11; 330